Erratum: LINDSAY W. POPPLE (2017) A revision of the Ewartia oldfieldi (Distant) species complex (Hemiptera: Cicadidae: Cicadettinae) with five new species from eastern and northern Australia. Zootaxa, 4263 (3): 401–449. - Popple, Lindsay W. (Zootaxa, 2025)
N/A